XPS study of sulfur and phosphorus compounds with different oxidation states - Kim, S Siow; Britcher, Leanne; Sunil Kumar,; Griesser, Hans J (Penerbit Universiti Kebangsaan Malaysia, 2018)
In this report, we demonstrate that continuous improvement in XPS instruments and the calibration standards as well as analysis with standard component-fitting procedures can be used to determine the binding energies of compounds containing phosphorus and sulfur of different oxidation states with higher confidence. Based on such improved XPS analyses, the binding energies (BEs) of S2p signals for sulfur of increasing oxidation state are determined to be 166-167.5 eV for S=O in dimethyl sulfoxide, 168.1 eV for S=O2 in polysulfone, 168.4 eV for SO3 in polystyrene sulfonate and 168.8 eV for SO4 in chondroitin sulfate. The BEs of P2p signals show the following values: 132.9 eV for PO3 in triisopropyl phosphite, 133.3 eV for PO4 in glycerol phosphate, 133.5 eV for PO4 in sodium tripolyphosphate and 134.0 eV for PO4 in sodium hexametaphosphate. These results showed that there are only small increases in the binding energy when additional oxygen atoms are added to the S-O chemical group. A similar result is obtained when the fourth oxygen or poly-phosphate environment is added to the phosphorus compound. These BE values are useful to researchers involved in identifying oxidation states of phosphorus and sulfur atoms commonly observed on modified surfaces and interfaces found in applications such as biomaterials, super-capacitors and catalysis.